Molecular and serological evidences of Midichloria mitochondrii transmission to vertebrate hosts during the tick bite. (International Journal of Health, Animal Science and Food Safety, 2016)
The tick Ixodes ricinus is vector of many pathogens important for human and animal health (Parolaand Raoult, 2001; Socolovschi, 2009). Midichloria mitochondrii (order Rickettsiales; familyMidichloriaceae) is an endosymbiont present in the salivary glands of 100% of Ixodes ricinus females.Two lines of evidence suggest a transmission of M. mitochondrii in mammalians during the tick bite: 1)detection of circulating DNA in blood samples of different animal species; 2) seropositivity toward aM. mitochondrii protein (FliD) in humans and dogs exposed to tick bite (Mariconti 2012; Bazzocchi2013). Here we present serological and molecular results demonstrating the circulation of M.mitochondrii also in Capreolus capreolus (the host of choice for adult and nymph stages of I. ricinus),confirming that this host is a good subject to study the spread of tick-borne pathogens.Based on these results, FliD protein and other M. mitochondrii markers could thus be extremely usefulto determine the risk of infection by I. ricinus pathogens in given areas, and for investigating theepidemiological association of a variety of pathological alterations with this tick.Here we show results of the screening of 218 human sera (50 from non endemic areas used as negativecontrols and 168 from subjects exposed to tick bite) collected in different areas of Germany. Resultsshowed that 48 out of 168 sera were positive to M. mitochondrii.These results have posed the basis for the development of a serological test for investigating theexposure of humans and animals to this tick species.
Keywords: Ixodes ricinus; Midichloria mitochondrii; Serological screening; Mammalian hosts; Marker